Synthesis of chalcone-containing methacrylate-based hydrogen bonded side chain liquid crystalline polymer and its dielectric properties - Korkmaz, Burak; Gursel, Yesim Hepuzer; Canli, Nimet Yilmaz; Ozdemir, Zeynep Guven; Okutan, Mustafa; Senkal, Bahire Filiz (WILEY, 2017)
In this work, a new methacrylate-based hydrogen bonded side chain liquid crystalline polymer having chalcone moieties (HBCP) was prepared from poly(4-(3-(pyridin-4-yl)acryloyl) phenyl methacrylate) and 11-(4-cyanobiphenyl-4(-oxy) undekan-1-ol (LC11)) by molecular self-assembly processes via hydrogen bond formation between nitrogen of the HBCP and hydroxyl group of the LC11. The formation of H bond was confirmed by using Fourier transform infrared (FTIR) spectroscopy. The phase transition temperatures and liquid crystalline phases of the HBCP were examined by DSC and POM measurements. The dielectric properties of HBCP have been determined by impedance analyzer within the frequency interval of 100Hz-15MHz. According to Cole-Cole plot, the equivalent circuit of the LC system has been found as a capacitor in parallel with a resistor. The resonance frequency, f(r), of the R-C circuit has also been calculated as 1.59MHz by phase angle versus frequency curve. The dielectric relaxation type of HBCP has been determined as nearly-Debye type because the absorption coefficient, , equals to 0.01655. From the conductivity point of view, HBCP displays dc conductivity at the low and high frequency regions that correspond to 100Hz-12kHz and 3.3MHz-15MHz, respectively. On the other hand, it has been revealed that the ac conductivity of the LC system investigated obeys Super Linear Power Law (SLPL) at the intermediate frequency domain. Copyright (c) 2015 John Wiley & Sons, Ltd.
Keywords: hydrogen bonding; liquid crystal polymers; chalcone polymers; dielectric properties; REVERSIBLE OPTICAL STORAGE; MESOGENIC ACIDS; AC-CONDUCTIVITY; AZO POLYMERS; PHOTOPOLYMER; COPOLYMERS; ALIGNMENT; Polymer Science